2019
DOI: 10.1016/j.idcr.2018.e00478
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar Typhi osteomyelitis in a young adult with sickle cell and thalassemia traits: A possible association

Abstract: Salmonella osteomyelitis is known to occur in immunocompromised and sickle cell disease patients. It rarely occurs in other hosts. We present a case of chronic femoral osteomyelitis due to S. enterica serovar Typhi seen in a Maryland resident. Potential risk factors included traveling to an endemic area as well as a newly diagnosed sickle cell trait and thalassemia trait. It is postulated that less severe hemoglobinopathies may also contribute to an elevated risk of Salmonella osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Arizonae and Salmonella Typhi [ 4 , 5 , 6 ]. Analysis of Salmonella Osteomyelitis by Stephanie and Schmalzle revealed that most of the osteomyelitis patients have an underlying predisposing condition such as sickle cell trait, thalassemia trait, and other hemoglobinopathes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arizonae and Salmonella Typhi [ 4 , 5 , 6 ]. Analysis of Salmonella Osteomyelitis by Stephanie and Schmalzle revealed that most of the osteomyelitis patients have an underlying predisposing condition such as sickle cell trait, thalassemia trait, and other hemoglobinopathes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Although she was incidentally diagnosed to have alpha 2-thalassemia minor, minor forms of the thalassemia trait as a predisposing factor for Salmonella infections are not as well described as underlying established hemoglobinopathies, such as sickle cell anemia, thalassemia with high iron load, or previous splenectomy. [23][24][25][26][27][28] Generally, NTS as a renal pathogen is unusual, and an occult urologic problem or an immunodeficiency should be considered. 16 Most reported pediatric renal abscess cases were managed with antibiotic therapy as a mainstay, and in some cases, with concomitant abscess drainage (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Other microorganisms include Escherichia coli, Streptococcus, Klebsiella and Proteus (Zhan et al 2018). Osteomyelitis caused by Salmonella has been reported sporadically (Hashimoto et al 2018;Stephanie and Schmalzle 2019;Zhan et al 2018), but little is known about its pathogenesis. Salmonella can cause a variety of clinical forms, including sepsis, typhoid fever, gastroenteritis, localized organ disease, and asymptomatic chronic carrier state (Zhan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, salmonella osteomyelitis is rare, accounting for only 0.8% of all cases of salmonella infection, and is the causal microorganism in 0.45% of all cases of osteomyelitis (Sanchez et al 1996). Salmonella osteomyelitis is predominantly common in patients with sickle cell disease or thalassemia and immunocompetent (Tóth et al 2002;Stephanie and Schmalzle 2019). Salmonella osteomyelitis is an infection of the long bones, primarily the diaphysis of the femur and humerus; other bones that are involved include the lumbar spine, tibia, radius, and ulna (McAnearney and McCall 2015).…”
Section: Introductionmentioning
confidence: 99%